(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
A major challenge of ocean wave energy converter (WEC) development is to test in the actual ocean. In this article, how a point absorber (PA) WEC was developed and tested during the mid of November 2022 in the ocean is reported. The WEC named Sindhuja-1 was developed from concept, numerical modelling, and laboratory testing. The test site was the VOC Port in Tuticorin, India. The WEC consisted of a buoy, a spar, and a power take-off mechanism. The buoy diameter was 0.75m and the spar length was 10m. The whole design was done at IIT Madras and preliminary tests were done at the wave basin at IIT Madras. The system was transported to the site and a preliminary test was conducted at the harbour area where the water is calm and has a depth of more than 10m. The purpose of the tests was to check any leakage, buoyance, and stability. After that, a hired fishing boat dragged the system over the ocean surface to a location where 20m water dept is there. The distance from the coast was 6km, and wave heights of approximately 0.5-0.8 meters. For the sea trial design, electronic items were insulated, and a cylindrical cover was also put over the electrical components to avoid water splashes or rain. It was found that the system worked vertically, and the system produced a power of about 100W. The paper will explain the challenges faced during the planning and execution of the system.